Outcome of loop cholecystojejunostomy as a palliative procedure in unresectable distal malignant biliary obstruction - S., Greeshma; Rajan, Ramesh; S., Chandrashekar; C., Jayan (International Surgery Journal, 2021)
Background: Up to 70-80% of patients with malignant biliary obstruction seek medical attention only at unresectable stage. Though R0 resection is the therapeutic modality, surgical palliation has a definite role for securing biliary bypass. Hepatico (choledocho) jejunostomy and cholecystojejunostomy are the procedures of choice. As loop CCJ is technically simple to perform as well as having less operating time and blood loss;anappealing choice. Aim of the current study was to assess the outcome of loop CCJ as a palliative procedure in unresectable distal malignant biliary obstruction. Methods: 25 patients who underwent loop CCJ for radiologically and histopathologically proven unresectable distal malignant biliary obstruction in GMC, Thiruvananthapuram, were studied for a period from 1st January 2015 to 31st December 2016. Each patient was followed up for 6 months post operatively for the occurrence of cholangitis, relief from pruritus, number of hospitalization, duration of hospital stay, postoperative 30 day mortality and life span. Pre and postoperative serum bilirubin were studied using paired t test. Palliative surgery outcome score was calculated to assess the outcome. Results: Serum bilirubin levels were significantly reduced postoperatively. Mean pre and post-operative total bilirubin values were 15.10±1.65 (mg/dl) and 4.30±3.04 (mg/dl) respectively with p<0.001. 80% had relief of pruritus and 96% were free of cholangitis 76% had a PSOS more than 0.7. Conclusions: Loop CCJ has acceptable outcome as a palliative option for surgical bypass to relieve jaundice, pruritus in patients with unresectable distal malignant biliary obstruction with a good PSOS. This procedure is technically simpler and having fewer incidences of post-operative cholangitis, pruritus, post-operative hospital stays as well as 30 day mortality.